Dynamic Permeability Related to Greisenization Reactions in Sn-W Ore Deposits: Quantitative Petrophysical and Experimental Evidence. (27th February 2019) - Launay, Gaëtan; Sizaret, Stanislas; Guillou-Frottier, Laurent; Fauguerolles, Colin; Champallier, Rémi; Gloaguen, Eric
Abstract : Massive greisens are commonly associated with Sn-W mineralization and constitute low-grade high-tonnage deposits. The formation of this type of deposit results from an intense pervasive metasomatic alteration involving a major fluid and mass transfer through a nominally impermeable parental granite. A decrease in the volume of the solid phases associated with the mineral replacement reactions may be a potential process for creating pathways to enhance fluid flow. Here, we explore the effects of the replacement reactions related to greisenization on the granite's mineralogy and petrophysical properties (density, porosity, and permeability), as well as their potential implications for fluid flow in the case of the world-class Panasqueira W-Sn-(Cu) deposit, Portugal. Mineralogical and microtextural analyses of greisenized facies show that the total replacement of feldspars by muscovite is associated with a volume decrease of the solid phases that induces a significant porosity generation in greisen (~8.5%). Greisenization experiments coupled with permeability measurements show that the replacement of feldspars by muscovite permits new pathways at the crystal scale that significantly enhance the transient permeability. Moreover, permeability measurements performed on representative samples with different degrees of greisenization show that permeability increases progressively with the level of alteration from 10 -20  m 2 in least granite to 10 -17  m 2 in greisen. The correlation between the permeability and porosity evolutions demonstrates that the porous texture developed during replacement reactions creates new pathways that enhance significantly the permeability in greisen systems. The occurrences of mineral-bearing metals such as cassiterite in the newly formed porosity of greisen provide evidence that greisenization can be a decisive process for enhancing fluid flow and promoting transport of metals in Sn-W deposits. Finally, we present a model involving a positive feedback between greisenization and permeability, in which mineralizing fluids are able to generate their own pathways in initially impermeable granite via replacement reactions, which in turn promote further hydrothermal alteration and mass transport.